Antecedents and impact of AIS usage amongst Jordanian SMEs : moderating effects of environmental uncertainty and firm size - Lutfi, Abd Alwali (2017)
An effective use of the Accounting Information System (AIS) facilitates firms to sustain their competitiveness by providing timely, accurate and reliable financial information for more informed business decisions. Despite extensive government efforts, the usage of AIS amongst the Small and Medium-sized Enterprises (SMEs) in Jordan is relatively low and thus limiting the impact on firms‘ effectiveness. Furthermore, previous studies regarding the antecedents and impact of AIS usage are somewhat inconsistent. Thus, the purpose of this study was to propose an integrated model utilizing the Technological, Organizational, and Environmental (TOE) framework and the Resource-based View (RBV) theory to better explain the antecedents affecting AIS usage and its impact on AIS effectiveness amongst Jordanian SMEs. This study hypothesized seven factors affecting AIS usage based on the TOE framework. Meanwhile, RBV explained the relationship between AIS usage and AIS effectiveness as well as the moderating effects of environmental uncertainty and firm size on such relationships. Using the quantitative approach, this study employed a self-administered questionnaire survey on 741 owners of SMEs listed in the Amman Chamber Industry, of which 186 responses were usable for analysis (25% response rate). The Partial Least Squares (PLS) results revealed significant influence of compatibility (technological factor), owner/manager commitment and organizational readiness (organizational factors), as well as competitive pressure and government support (environmental factors) on AIS usage. Furthermore, compatibility demonstrated the strongest influence on AIS usage followed by competitive pressure. The results further demonstrated a positive and significant effect of AIS usage on AIS effectiveness. Finally, the findings only ascertained considerable moderating effect of firm size. Apart from extending the body of knowledge by providing a comprehensive model to explain how several interrelated factors influence AIS usage and its impact on AIS effectiveness, the results offer insights on how firms could improve the use of AIS for better firms‘ performance.